Perbaikan Sistem Operasi Component Part Order (CPO) Untuk Menghilangkan Process Delay dan System Error Pada Kegiatan Ekspor PT Toyota Motor Manufacturing Indonesia - Lucy Sanjaya; I Gede Agus Widyadana (Jurnal Titra, 2018)
PT Toyota Motor Manufacturing Indonesia (TMMIN) is an automotive company in Indonesia that operates as a manufacturer and exporter of Toyota products and spare parts. One of TMMIN’s export activity is Component Part Order (CPO). CPO handling is done using the help of the system, but the current system has problems, which is the occurrence of system errors. The current system is also not able to display tracking order visualization so there is often a process delay occurs in handling CPO. Analysis of the cause of process delay is done using Toyota Business Practice (TBP) and Ishikawa Diagram. Improvements made is to design a new system so that system error problems that occur in the old system can be eliminated. The system is also designed to have an order tracking function so that every process of CPO handling can be recorded in the system. Improvements to deal with CPO operational issues are also designed in the system. Goals of this improvement is to achieve a smooth and on time CPO handling. Another expected advantage of this improvement is the saving of 2244 hours / year of work time required to solve the problem.